Misteli on vakiintumassa Suomeen - Jouni Issakainen; Kati Pihlaja; Aarno Kasvi (Luonnontieteellinen museo, 2022)
Mistletoe (Viscum album) has during the 2010’s been spreading in the vicinity of Turku (Varsinais-Suomi, Finland). This is the first known fertile V. album population within the country. The situation in 2018 is mapped here, with a review of the biology and dispersal of this hemi-parasitic species. V. album was found at 48 locations, with the total number of shoots (seed-originating clones) being 307. The plants were
still young and mostly sterile. The most common host trees noted were Populus, Malus, Sorbus, Tilia and Acer species, all growing in open sites on the edges of  inhabited areas. The findings are consistent with
first-generation seedlings, dispersed by birds from a common mother population. A candidate for such a population was located within the town of Naantali. The lack of Viscum album sightings in the surrounding districts would indicate that the current dispersal originates from mistletoe imported for decoration.
The prospects of future dispersal in Finland are discussed, including the suitability of local host trees and the behaviour of birds.